Contemporary Rates of Preoperative Cardiac Testing Prior to Inpatient Hip Fracture Surgery. Issue 4 (20th February 2019) - Ellenbogen, Michael I; Brotman, Daniel J; Prichett, Laura; Li, Ximin; Feldman, Leonard S
Abstract : Hip fracture is a common reason for urgent inpatient surgery. In the past few years, several professional societies have identified preoperative echocardiography and stress testing for noncardiac surgeries as low‐value diagnostics. We utilized data on hospitalizations with a primary diagnosis of hip fracture surgery between 2011 and 2015 from the State Inpatient Databases (SID) of Maryland, New Jersey, and Washington, combined with data on hospital characteristics from the American Hospital Association (AHA). We found that the rate of preoperative ischemic testing is surprisingly but encouragingly low (stress tests 1.1% and cardiac catheterizations 0.5%), which is consistent with studies evaluating the outpatient utilization of these tests for low‐ and intermediate‐risk surgeries. The rate of echocardiograms was 12.6%, which was higher than other published reports. Our findings emphasize the importance of ensuring that quality improvement efforts are directed toward areas where quality improvement is, in fact, needed.